Periodic Solutions of Second-Order Differential Inclusions Systems with -Laplacian - Liang Zhang; Peng Zhang (Abstract and Applied Analysis)
The existence of periodic solutions for nonautonomous second-order differential inclusion systems with -Laplacian is considered. We get some existence results of periodic solutions for system, a.e. , , by using nonsmooth critical point theory. Our results generalize and improve some theorems in the literature.